Preliminary Design of Autonomous Underwater Vehicle with Higher Resolution Underwater Camera for Marine Exploration - Salleh, Z.; Ghani, M.F.; Ramli, M.A.H. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2013)
This research explains on a design and development of an Autonomous Underwater Vehicle (AUV). Definition of AUV is a robotic sub-sea that is a part of the emerging field of autonomous and unmanned vehicles. This project shows the design of implementation of an AUV as a test prototyping vehicle especially involved small-scale and low cost sub-sea robots. The AUV prototype has been design and simulate by using SolidWorks. The AUV assembled with mechanical system, module of electronic system for development of controller.